Correlation of Magnetic Resonance Spectroscopy and Perfusion at Non-Enhancing Edematous Area in High-Grade Glioma for Tumor Recurrence After Maximal Safe Resection - Kittipong, Thongnual; Theerapol, Witthiwej; Orasa, Chawalparit; Siriwan, Piyapittayanan; Tumtip, Sangruji (Thai Journal of Neurological Surgery, 2016)